Optimization and Decision-Making for a Service Contract on Machine Maintenance - Zeyu Luo; Zhixin Yang; Jinbiao Wu; Zhaotong Lian (Operations Research and Decisions)
We investigate a novel maintenance service contract model. The service provider of the machine must determine the optimal pricing structure and staffing levels, while the client selects an appropriate plan for the warranty duration. We consider linear, quadratic, polynomial, and exponential pricing functions for three types of warranties. By building a service model with a non-cooperative game, we obtain the Nash equilibrium of the bargaining solution. Numerical analysis reveals that the optimal warranty period decreases monotonically with service provider revenue and increases monotonically with the maximum prospective service time. Additionally, the market size does not affect the ideal warranty duration when the machine's lifetime is constant. (original abstract)